Peningkatan Kemampuan Bahasa Arab Santri melalui Implementasi Program Pusat Studi Bahasa Asing (PUSBA): Studi Pengabdian di Pondok Pesantren Jalaluddin Arrumi - M. Naufal Al Qurthuby Fuady S; Nuril Mufidah; Abdul Malik Karim Amrullah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The Foreign Language Study Center (PUSBA) program at the Jalaluddin Arrumi Jatisari Islamic Boarding School in Jenggawah, Jember, is a form of community service aimed at improving students' Arabic language skills as a key resource for facing global challenges. The program aims to describe the implementation and impact of the PUSBA program as a structured and sustainable community service effort. Activities are implemented through a participatory approach and intensive training methods that include direct learning, mentoring by ustadz/ustadzah, and the integration of language practices into daily life within the Islamic boarding school environment. The implementation process involves participant selection, the development of a tiered curriculum, and the establishment of a collaborative implementation structure. The program's impact is evident in the students' increased motivation to use Arabic in daily interactions, positive changes in language habits, and the development of concrete skills such as active conversation, translation, and simple writing. Qualitative data from interviews and observations indicate that students experience increased confidence in using Arabic and the formation of a conducive language culture within the Islamic boarding school environment. This program has succeeded in creating an effective community-based learning model in strengthening the language capacity of community partners.